Radical-Mediated Hetaryl Functionalization of Nonactivated Alkenes through Distal ipso-Migration of O- or S-Hetaryls - Zhang, Huihui; Ji, Meishan; Wei, Youhao; Chen, Haodong; Wu, Xinxin; Zhu, Chen (Synlett, 2020)
A radical-mediated hetaryl functionalization of nonactivated alkenes through distal ipso-migration of O- or S-containing hetaryls was developed. Furyl, benzofuryl, thienyl, and benzothienyl groups showed satisfactory migratory abilities. A variety of heteroatom-centered radicals, including azido, trifluoromethylsulfanyl, and silyl radicals readily trigger the migration cascade, and a new C–heteroatom and C–C bond are concomitantly constructed in the reaction. This method provides an efficient approach to the synthesis of high-valued complex O- or S-hetaryl compounds.
Keywords: hetaryl compounds; alkene difunctionalization; functional-group migration; radical reaction; radicals; rearrangement